Effective Factors related to Fast-foods Consumption in Bandar Abbas: A Community-Based Study - Sakineh Dadipoor; Abdoulhhossain Madani; Amin Ghanbarnejad; Ali Safari Moradabadi; Firouz Amani; Marzieh Hosseini; Hamideh Yeganeh (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: In recent decades there has been a growing increase in the consumption of fast-foods. As a result of over-consumption of these high-calorie and fatty foods and the unbalance between the received and consumed energy, the chance of affliction with cardiovascular diseases and diabetes in individuals has rised. The present research sought to determine the effective factors related to the consumption of fast-foods in Bandar Abbas in 2013. Methods: The present research was descriptive/analytic and of a cross-sectional type. Research population was comprised of 600 fast-food consumers. The samples were selected using a combination of cluster sampling and convenient sampling. The instrument used for gathering data was a researcher-made questionnaire (RMQ) to measure the reasons for people's tendency toward consuming fast-foods. The validity of the questionnaire was confirmed by experts and its reliability was established in the pilot study. SPSS16 was used to analyze the data. Descriptive statistics (mean, SD, frequency and percentage) as well as analytical statistics (ANOVA and Chi-squared test) were used. Significance level was set at <0.05. Results: 52% of subjects were male and 303 (50.5%) of them preferred pizza among fast-foods. Fast-food consumption was most prevalent among individuals below 25 years of age. Subjects with university degrees consumed fast-food more than others. Conclusion: Consuming fast-foods was more prevalent among youngster and those with academic degrees. Place of residence, education and employment could be involved in the recurrent consumption of fast foods. Paper Type: Research Article